Tuning of a new fuzzy bang-bang relay controller for attitude control system - Nagi F.; Bin Zainul Abidin A.A.; Zulkarnain A.T.; Nagi J.; Marwan A. (Inderscience Publishers, 2023)
A new fuzzy bang-bang relay controller (FBBRC) is introduced in this paper. The new controller is inherently optimal due to its bang-bang property. The controller has fuzzy decision-making capability in its inputs and have two fixed levels bang-bang output. Consequently, the tuning of FBBRC is restricted to input parameters only in comparison to standard fuzzy logic controller (FLC) where the output parameters can also be tuned. The stability of new controller stems from well-established bang-bang sliding mode control theory. The work presented here demonstrates that tuning the inputs of the proposed FBBRC is more effective and simpler than tuning all the parameters of standard FLC. The two controllers are tuned online with gradient descent optimisation method and tested for regulator and tracking mode control. Simulation result shows that new controller has faster response time and is capable of controlling the system under adverse initial conditions. Copyright 2011 Inderscience Enterprises Ltd.